2022
DOI: 10.1016/j.nedt.2022.105277
|View full text |Cite
|
Sign up to set email alerts
|

Salutogenesis and COVID-19 pandemic impacting nursing education across SEANERN affiliated universities: A multi-national study

Abstract: Background The COVID-19 pandemic has disrupted the lives of many. Particularly, nursing students experience greater stress as their normal curriculum is interrupted and some of them face the risk of being infected as frontline workers. Nursing faculty members may face similar struggles, in addition to developing teaching materials for online learning. Thus, it is important to examine the faculty members' and students' views on their ability to adapt during the pandemic to obtain a holistic view of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
0
18
1
6
Order By: Relevance
“…These findings echo those of studies across the globe suggesting a common experience regardless of race or ethnicity (Cengiz et al, 2022 ; Fitzgerald & Konrad, 2021 ; Heilferty et al, 2021 ; Wallace et al, 2021 ; Yazici & Ökten, 2022 ). However, while other studies have documented mild to moderate levels of student anxiety and fear during the pandemic (Shorey et al, 2022 ; Yazici & Ökten, 2022 ), students in this study described more severe experiences of anxiety and psychological distress emphasizing the need for more comprehensive and mental health assessments and resources in nursing education.…”
Section: Discussioncontrasting
confidence: 68%
“…These findings echo those of studies across the globe suggesting a common experience regardless of race or ethnicity (Cengiz et al, 2022 ; Fitzgerald & Konrad, 2021 ; Heilferty et al, 2021 ; Wallace et al, 2021 ; Yazici & Ökten, 2022 ). However, while other studies have documented mild to moderate levels of student anxiety and fear during the pandemic (Shorey et al, 2022 ; Yazici & Ökten, 2022 ), students in this study described more severe experiences of anxiety and psychological distress emphasizing the need for more comprehensive and mental health assessments and resources in nursing education.…”
Section: Discussioncontrasting
confidence: 68%
“…It was assumed that a person with a high Sense of Coherence would find meaning also in the COVID-19 distancing, understand its necessity, and manage one's life in the new situation. In earlier studies, SOC has been related to lower levels of COVID-19 pandemic related to stress, anxiety, and depression among students (Li et al, 2021;Misamer et al, 2021;Shorey et al, 2022). In addition, SOC seems to reduce COVID-19 related fears among teachers (Padmanabhanunni et al, 2022) and help to adjust to the post-covid face-to-face education (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…SOC includes three interrelated components: Comprehensibility (i.e., seeing life as understandable), Manageability (i.e., feeling of having resources and skills to cope with stressful events in life), and Meaningfulness (i.e., seeing life as worthy and full of motivation). Earlier studies conducted in educational settings have found that a high Sense of Coherence is related lower COVID-19 related depression, anxiety, and stress among college students (Li et al, 2021; Shorey et al, 2022). Especially the sense of meaningfulness seems to be an important protective factor among students (Misamer et al, 2021) and teachers (Padmanabhanunni et al, 2022).…”
Section: Introductionmentioning
confidence: 91%
“…3 Even before the pandemic, some literature has uncovered themes related to student challenges to online learning, including technological barriers, student/instructor communication barriers, and difficulties in engaging students. 4 Nursing students are currently in the midst of experiencing a profound transition from in-person learning to online learning that requires them to incorporate new knowledge and change their behavior. Transition theory is explained by 5 as a college nursing education center requires new knowledge, changing behavior, and even changing self-definition.…”
Section: Introductionmentioning
confidence: 99%